2011
DOI: 10.1002/cncr.26267
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of patient navigation

Abstract: Background The lack of comparable metrics to evaluate prevention and early detection patient navigation programs impedes our ability to identify best practices. Methods The Prevention and Early Detection Workgroup of the Patient Navigation Leadership Summit was charged with making recommendations for common metrics specific to the prevention and early detection phase of the cancer care continuum. The workgroup began with a review of existing literature to characterize variability in published navigation metr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…14 This is particularly true for managing cancer care where navigation has a unique role in improving the overall health of the patient, family and community at large through efforts in cancer prevention and early detection, cancer care access and coordination, insurance coverage and continuity, identification and referral to cancer resources and support services, and palliative and end-of-life care. Patient navigators, particularly those from the same community or with the same or similar cultural background, can reduce fear and anxiety, build trust, decrease literacy barriers, facilitate patient-provider communication, provide psychoemotional support and manage logistical obstacles to cancer care.…”
Section: Patient Navigation To Reduce Health Inequitiesmentioning
confidence: 99%
“…14 This is particularly true for managing cancer care where navigation has a unique role in improving the overall health of the patient, family and community at large through efforts in cancer prevention and early detection, cancer care access and coordination, insurance coverage and continuity, identification and referral to cancer resources and support services, and palliative and end-of-life care. Patient navigators, particularly those from the same community or with the same or similar cultural background, can reduce fear and anxiety, build trust, decrease literacy barriers, facilitate patient-provider communication, provide psychoemotional support and manage logistical obstacles to cancer care.…”
Section: Patient Navigation To Reduce Health Inequitiesmentioning
confidence: 99%
“…More information is needed to determine the reliability and validity of the instrument. Battaglia, Burhansstipanov, Murrell, Dwyer, and Caron (2011) reported that the lack of comparable metrics in diverse programs limits the goal of identifying best practices. This challenge must be addressed as navigation becomes assimilated into universal standard care services.…”
Section: Implications For Practicementioning
confidence: 99%
“…This challenge must be addressed as navigation becomes assimilated into universal standard care services. A Prevention and Early Detection Workgroup is identifying metrics that are tailored to cancer prevention and detection across that cancer care continuum (Battaglia et al, 2011). According to Guadagnolo, Dohan, and Raich (2011), institution-specific baselines need to be specified to measure metrics, such as timeliness of care.…”
Section: Implications For Practicementioning
confidence: 99%
“…When able to make contact, the navigator identified and addressed individual barriers to care, such as transportation, language, insurance, work scheduling conflicts, and fear. The PN documented her encounters in the electronic medical record (EMR) using a standardized navigator tracking log (Battaglia et al, 2011;Freund et al, 2008).…”
Section: Pn Interventionmentioning
confidence: 99%